Wearable Electronics: Polymer‐Enhanced Highly Stretchable Conductive Fiber Strain Sensor Used for Electronic Data Gloves (Adv. Mater. Technol. 7/2016). Issue 7 (14th October 2016) - Chen, Shuai; Lou, Zheng; Chen, Di; Jiang, Kai; Shen, Guozhen
Abstract : In article number 1600136, the fabrication of a conductive strain sensor with high sensitivity, good stability and excellent flexibility is reported by Kai Jiang, Guozhen Shen, and co‐workers. This holds great promises for applications such as human motion detection, health monitoring and human‐machine interfacing devices.